Belize. Significant achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Belize during 2020 are identified, with respect to the needs and interests of the country, identifying problems in adaptive technologies for family farming, climate change, food security,. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized. Finally, projects were executed in the direction of financing for the recovery of the rural sector due to the post-COVID-19.